Optimization and Utilization of Tofu Waste by Using Separator Machine Technology to Increase the Income of Home Industries and Create Environment-Friendly Industries Through Diversification of Various Foods Processing - Nely Ana Mufarida; Diyah Probowulan (Kontribusia : Research Dissemination for Community Development, 2019)
Tofu industry is one of the big producers of waste because the waste reachs 25-35% of tofu product. TheLack of public awarness about the tofu waste resulted unused waste, even they throw away the tofu waste withoutknowing the high nutrition contained in the tofu waste. Cooperation between UD. The final target to be achieved is toform a business unit for various processed foods using a separator machine in the sanding of tofu waste with soy milkextract, as well as marketing management with the help of information technology (social media). The basiccontribution to the target is that housewives get new knowledge and skills about diversifying various processed tofuwaste products and getting more benefit. In addition, housewives will get income from creative economic activitiesfor the sake of moving the economic wheel that increases directly for the community, especially families.